Genetic fingerprinting and antimicrobial susceptibility profiles of pseudomonas seruginosa hospital isolates in Malaysia - Lim, King Ting; Yasin, Rohani Md; Yeo, Chew Chieng; Puthucheary, Savithri Devi; Balan, Ganeswrie; Maning, Nurahan; Wahab, Zubaidah Abdul; Ismail, Noraini; Tan, Eng Am; Mustaffa, Azizah; Thong, Kwai Lin (Elsevier, 2009)
Background and purpose: Pseudomonas aeruginosa is the third most common pathogen causing nosocomial infections. The objective of this study was to investigate the antimicrobial resistance profiles and genetic diversity of hospital isolates of P. aeruginosa and to investigate the presence of several resistance genes and integrons. Methods: In this retrospective study, 48 clinical isolates of P. aeruginosa from 6 public hospitals in Malaysia were analyzed by antimicrobial susceptibility test and DNA fingerprinting techniques. Results: Most of the P. aeruginosa isolates were resistant to tetracycline (73) and chloramphenicol (60) and, to a lesser extent, cefotaxime (40), ceftriaxone (31), cefoperazone (29), ticarcillin (25), piperacillin (23), and imipenem (21). Less than 20 of the isolates were resistant to ceftazidime, gentamicin, cefepime, ciprofloxacin, amikacin, piperacillin-tazobactam, and aztreonam (10). Of the 48 isolates, 33 were multidrug resistant. Two isolates were extended-spectrum beta-lactamase (ESBL) producers using the double-disk synergy test. However, polymerase chain reaction (PCR) failed to detect any common ESBL-encoding genes in all isolates, except for bl(OXA-10) in PA7 that was found to be part of a class 1 integron-encoded aacA4-bla(IMP-9)-catB8-bla(OXA-10) gene cassette. Using PCR, class 1 integron-encoded integrases were detected in 19 of the P aeruginosa isolates. Repetitive extragenic palindrome-PCR generated 40 different profiles (F = 0.50-1.0) and enterobacterial repetitive intergenic consensus-PCR produced 46 profiles (F = 0.51-1.0). Pulsed-field gel electrophoresis with Spel-digested genomic DNA resulted in 45 different profiles (F = 0.50-1.00). Conclusion: Aztreonam appeared to be the most effective agent against multidrug-resistant P. aeruginosa isolates. Sixty nine percent of the P aeruginosa isolates analyzed were multidrug resistant and the isolates were genetically diverse.